MODERN ASPECTS OF NEBULIZER THERAPY - Svetlana N. Buynova (Байкальский медицинский журнал)
Nebulizer therapy is widely used in modern respiratory medicine. Nebulizers are devices that convert a liquid into a suitable for inhalation by a patient aerosol, which meets the requirements of the European standard for nebulizer therapy prEN 13544-1. The fundamental differences between nebulizers and other inhalation devices (metered aerosol inhalers, powder inhalers) are the possibility to perform maneuvers on spontaneous breathing, the use of drugs, which do not involve the use of other inhalers, and the possibility to select drug doses depending on patients need.Although this delivery method is effective for many respiratory diseases, and it is preferred for special groups (children, the elderly, as well as severe exacerbations, etc.), there are some peculiarities and limitations of its use, which should be taken into account by clinicians. According to the principle of operation, nebulizers are divided into compressor, ultrasonic and electronic-mesh, which differ in technical characteristics and indications for use. Compressor nebulizers are most widely used in medical institutions (intensive care units, hospitals, offices) and at home, relatively inexpensive, simple and easy to maintain, have additional components (chambers with inhalation-exhalation valves, masks for children and children) adults, nasal aspirator, etc.). Modern jet nebulizers are equipped with spray mode switches, so that the aerosol feed rate and the aerodynamic diameter of particles of an average mass from 2-3 to 10 microns can be adjusted. Depending on the selection of the switch mode and the corresponding medication, the nebulizer can be used in the treatment of rhinitis, laryngitis, bronchitis, asthma and other diseases of both upper and lower respiratory tract.